EVALUATION OF ANTIANXIETY, ANTIDEPRESSANT AND SEDATIVE EFFECTS OF NIMODIPINE IN SWISS ALBINO MICE - Tanwani, Hemant; Nyati, Prem; Atal, Shubham; Churihar, Ritesh (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Study of Nimodipine, a calcium channel blocker was done on experiments involving tail suspension test (TST), elevated plus maze (EPM) test and Phenobarbitone induced sleeping time in Swiss albino mice. Methods: Nimodipine was given by intraperitoneal (i. p.) route in the dose of 2.5 & 5 mg/kg body wt respectively in albino mice of either sex (n=6) and effects were evaluated on (i) TST for antidepressant activity (ii) EPM for anti-anxiety and (iii) Loss of righting reflex for hypnotic activity and results were compared with the standard drugs like sertraline, diazepam and phenobarbitone respectively. Statistical analysis was done by ANOVA followed by Post hoc Tukey's test using SPSS v.20.0 software. Results: Nimodipine at a dose of 2.5 mg/kg has shown moderate anti-anxiety and antidepressant activities compared to control with no changes in the activity of acute sertraline; however, the antidepressant activity of subacute sertraline (14 d treatment) was summed up by 2.5 mg/kg dose without any hypnosis. While at higher doses of 5 mg/kg depression, behavior (prolonged time of immobilization on TST) and sedation (prolonged phenobarbitone induced sleep time) were seen. Conclusion: Nimodipine has shown moderate antidepressant and anti-anxiety activities at low doses and can be used as add-on therapy to routine drugs with least of peripheral side effects. Keywords: Nimodipine, Diazepam, Sertraline, Elevated plus maze (EPM), Tail suspension test (TST) and righting reflex